Just because a=10 does not mean 32 =10. 32 = 9, so the initial equation because 9 = a-1 or a-1 =9. This equations ask the question what - 1 = 9. Since what = 10 (since 10-1=9) and what is a, we have a=10.(3)2 = a-1
a=10
Could someoneasily tell me how'd the three squared turned into a ten? I mean wasen't the negative plus the negative suppose you give you a negative.
\(\displaystyle 3^2 = a - 1 \implies 9 = a - 1 \implies 9 + 1 = a - 1 + 1 \implies 10 = a + 0 \implies a = 10.\)(3)2 = a-1
a=10
Could someoneasily tell me how'd the three squared turned into a ten? I mean wasen't the negative plus the negative suppose you give you a negative.
\(\displaystyle 3^2 = a - 1 \implies 9 = a - 1 \implies 9 + 1 = a - 1 + 1 \implies 10 = a + 0 \implies a = 10.\)
No need to isolate the a.I understand it now. Thank you
I wasn'the isolating the a correctly.